2015
DOI: 10.4067/s0717-95022015000200021
|View full text |Cite
|
Sign up to set email alerts
|

Dental Morphological Markers as a Proxy for Ethnicity in Robinson Crusoe Islanders

Abstract: SUMMARY:Chilean Robinson Crusoe Island is a semi-isolated location with unusually high rates of both consanguinity and language disorder. The current population of 633 inhabitants is descended almost exclusively from the colonization at the end of the 19th century, as there were few preceding immigrations to the island. This study investigates the genetic composition and degree of miscegenation within the island population, using dental morphological markers. The universe of island children was studied (n= 128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…Dentro de los factores que pueden causar un RL se encuentra el retraso madurativo, los factores socioculturales o del entorno lingüístico (estilos comunicativos de la familia, prácticas de alfabetización temprana en el hogar, bilingüismo deficiente, entre otros) (Acosta Rodríguez et al, 2012;Monfort y Juárez Sánchez, 2013). En el TEL se plantea como posible etiología la genética (Villanueva et al, 2008;Villanueva et al, 2015); así, los antecedentes familiares son un factor de riesgo relevante (Acosta Rodríguez y Ramírez . Por otra parte, los niños y niñas que presentan RL manifiestan una evolución siempre favorable al recibir una estimulación general del lenguaje, por lo que se le considera una dificultad transitoria (Aguado Alonso, 2016).…”
Section: Retraso De Lenguaje Y Trastorno Específico De Lenguajeunclassified
“…Dentro de los factores que pueden causar un RL se encuentra el retraso madurativo, los factores socioculturales o del entorno lingüístico (estilos comunicativos de la familia, prácticas de alfabetización temprana en el hogar, bilingüismo deficiente, entre otros) (Acosta Rodríguez et al, 2012;Monfort y Juárez Sánchez, 2013). En el TEL se plantea como posible etiología la genética (Villanueva et al, 2008;Villanueva et al, 2015); así, los antecedentes familiares son un factor de riesgo relevante (Acosta Rodríguez y Ramírez . Por otra parte, los niños y niñas que presentan RL manifiestan una evolución siempre favorable al recibir una estimulación general del lenguaje, por lo que se le considera una dificultad transitoria (Aguado Alonso, 2016).…”
Section: Retraso De Lenguaje Y Trastorno Específico De Lenguajeunclassified
“…incisivos en pala). Si bien se trata de rasgos de expresión variable, han sido empleados con éxito para caracterizar y comparar poblaciones, así como establecer medidas de distancia biológica (Villanueva et al, 2015). La bibliografía regional, en general, no especifica en cuanto a este tipo de rasgos morfológicos no métricos (cf.…”
Section: Discusión Y Consideracionesunclassified
“…A previous dental morphology study tested 100 RCI children, using shovel-shaped incisor tooth as a proxy for native ancestry and Carabelli's cusp as a marker for European ancestry to estimate the ethnicity of the island population (Villanueva et al, 2015b). They found that the islanders predominantly had the European tooth morphology, and estimated indigenous ancestry at 4.3%.…”
Section: Indigenous Admixturementioning
confidence: 99%